2011
DOI: 10.1007/s10509-011-0780-0
|View full text |Cite
|
Sign up to set email alerts
|

Charged analogues of Schwarzschild interior solution in terms of pressure

Abstract: Recently, Bijalwan (Astrophys. Space Sci., doi: 10.1007/s10509-011-0691-0, 2011a) discussed charged fluid spheres with pressure while Bijalwan and Gupta (Astrophys. Space Sci. 317, 251-260, 2008) suggested using a monotonically decreasing function f to generate all possible physically viable charged analogues of Schwarzschild interior solutions analytically. They discussed some previously known and new solutions for Schwarzschild parameter u(= GM c 2 a ) ≤ 0.142, a being radius of star. In this paper we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Known applicable analytic solutions include [4,5,22]: In contrast, as far the literature is concerned known to the present authors, the charged analogs of Tolman's models (V-VI) obtained in [95][96][97][98][99][100][101] are not physically viable in the description of compact astrophysical objects as regards the infinite values of the central density and pressure. Though the Schwarzschild constant density solution is physically unrealistic, the charged analogs, obtained in [56,[102][103][104], and the charged analog of the Matese and Whitman solution, obtained in [105], may be relevant in the description of self-bound electrically charged strange quark stars. Charged analogs of the Tolman IV and VII models [106][107][108]), as the neutral ones, exhibit the physical features required for the construction of a physically realizable relativistic compact stellar structure.…”
Section: Introductionmentioning
confidence: 98%
“…Known applicable analytic solutions include [4,5,22]: In contrast, as far the literature is concerned known to the present authors, the charged analogs of Tolman's models (V-VI) obtained in [95][96][97][98][99][100][101] are not physically viable in the description of compact astrophysical objects as regards the infinite values of the central density and pressure. Though the Schwarzschild constant density solution is physically unrealistic, the charged analogs, obtained in [56,[102][103][104], and the charged analog of the Matese and Whitman solution, obtained in [105], may be relevant in the description of self-bound electrically charged strange quark stars. Charged analogs of the Tolman IV and VII models [106][107][108]), as the neutral ones, exhibit the physical features required for the construction of a physically realizable relativistic compact stellar structure.…”
Section: Introductionmentioning
confidence: 98%
“…So, none of the charged fluid solutions with (2.8b) has a well behaved neutral counter part in present case. Some of the special cases are discussed in Bijalwan (2011bBijalwan ( , 2011cBijalwan ( , 2011d. Bijalwan (2011d) showed that these solutions mimic classical electron model.…”
Section: Case Imentioning
confidence: 96%
“…Case A: Consider the solution derived by Bijalwan (2011c). The various parameters are written as e −λ = 1 − r 2 /R 2 , e υ = y 2 ,…”
Section: Appendixmentioning
confidence: 99%
See 2 more Smart Citations